A5_5 How big are the planets, really? - Scanlan, Fraser RJ; Howe, Rebecca; Javaid, Rafia; Pitts, Michael J (Physics Special Topics, 2017)
In this paper, we investigate the discrepancies in circumference of the planets in the Solar System that arise due to relativistic length contraction caused by their angular velocities. We then compare these discrepancies with the aim of creating a new method of comparison for different celestial bodies